The Application of Technology, Pedagogy, Content, Knowledge (TPACK) During The COVID-19 Pandemic - Ambar Sri Lestari (STAI Ma'had Aly Al-Hikam Malang, 2022)
This study aims to explore the application of TPACK during the Covid-19 pandemic in online learning. This research used narrative interviewing to analysis data. The participants were students and lecture who participated in online learning, with data collection interview with some lecture and student. The student’s participants in this study were willing to respond utilized Google Forms with open questions for collecting data. The research findings that students’ responses to the learning plan, learning content, learning strategies, class management, learning assessments, and supporting skills. It can be seen that student responses to the application of TPACK were based on online learning during the pandemic. The results showed three issues i.e. pedagogy knowledge, content knowledge and technical knowledge which were described in several indicators i.e. lesson plan, content material, teaching strategies, assessment, class management, and supporting skills. The mastery of TPACK itself was still not fully understood and conducted by lecturers in integrating technology-based material due to time constraints, lack of creativity in designing, and lecturers are more comfortable using conventional methods in delivering material, namely PowerPoint. This research implied that online learning changes not yet increased the lecturers’ creativity in designing teaching materials. Even though they obtained knowledge from attending workshops on teaching material design, lecturers still need assistance designing teaching materials according to the TPACK consept.